(untitled) - Michael, Alex (Elsevier, 2003)
Alex Michael and Ben Salter guide readers through proven techniques for achieving and measuring success, along with a review of the most important search engines and directories. Throughout the book there are numerous real case studies and tips to help the marketer build a world class web presence. Explains why and how marketers can and must optimize sites for searchability from the outset; Describes how to optimize, for both local and international users; Uses tutorials and walkthroughs to demonstrate how to steadily improve your site rankings
Keywords: Internet marketing,Web search engines